Q-SHINE: A versatile sensor for glutamine measurement via ligand-induced dimerization - Lim, Yun; Kim, Ji Yul; Jung, Youn Hee; Lee, Jae Hoon; Baek, Min Seok; Jung, Je Hyeong; Kim, Ho-Youn; Lee, Wookbin; Park, Keunwan; Seo, Moon-Hyeong (Elsevier BV, 2023)
Studies on glutamine (Gln) metabolism have highlighted the vital role of Gln in cellular functions and its potential as a biomarker for disease detection. Despite the increasing interest in Gln metabolism, in-depth evaluations are challenging owing to the limitations of conventional Gln-measuring methods. Thus, we developed a ligand-induced dimerization-based sensor for Gln, termed Q-SHINE, by splitting a glutamine-binding protein into two separate domains. Q-SHINE enables the highly accurate and convenient measurement of Gln concentrations in bio-fluid samples, with an optimal detection range for physiological Gln levels. Genetically encoded Q-SHINE sensors could also visualize intracellular Gln levels and quantify cytoplasmic and mitochondrial Gln changes in living cells, enabling the detection of various cell responses to extracellular Gln supplementation.